How Will Baseflow Respond to Climate Change in the Upper Colorado River Basin?. Issue 22 (22nd November 2021) - Miller, Olivia L.; Miller, Matthew P.; Longley, Patrick C.; Alder, Jay R.; Bearup, Lindsay A.; Pruitt, Tom; Jones, Daniel K.; Putman, Annie L.; Rumsey, Christine A.; McKinney, Tim
Abstract: Baseflow is critical to sustaining streamflow in the Upper Colorado River Basin. Therefore, effective water resources management requires estimates of baseflow response to climatic changes. This study provides the first estimates of projected baseflow changes from historical (1984–2012) to thirty‐year periods centered around 2030, 2050, and 2080 under warm/wet, median, and hot/dry climatic conditions using a hybrid statistical‐deterministic baseflow model. Total baseflow supplied to the Lower Colorado River Basin may decline by up to 33%, although this value may increase in the near future by 6% under warm/wet conditions. The percentage of baseflow lost during in‐stream transport is projected to increase by 1%–5% relative to historical conditions. Results highlight that climate‐driven changes in high‐elevation hydrology have impacts on basinwide water availability. Study results have implications for human and ecological water availability in one of the most heavily managed watersheds in the world. Plain Language Summary: Baseflow (groundwater flowing to streams) is estimated to contribute over 50% of the total streamflow in the Upper Colorado River Basin and is thus crucial for sustaining ecological and human water needs in this highly managed area. Baseflow may be sensitive to changing climate, but the sensitivity is not well constrained. To estimate baseflow response to climate change, we tested how warm/wet, median, and hot/dry future climate scenarios affect baseflow in the basin using a hydrologic model. Results show that the largest declines in baseflow may occur in the headwater streams, and the total baseflow delivered to the Lower Colorado River Basin may decline by up to 33%, although delivery may increase in the near future by 6% under a warm/wet climate. We hypothesize that basinwide baseflow declines because of greater increases in evapotranspiration relative to precipitation in the future. Baseflow loss during in‐stream transport is projected to increase by 1%–5%. The changes in baseflow may affect both human and ecological water users in an area where water supply does not always meet demand. Key Points: Upper Colorado River Basin deliveries to the Lower Colorado River Basin are projected to decline by the end of the 21st century despite potential increases in precipitation and baseflow in some areas The largest baseflow changes are projected to occur in higher elevation headwater catchments and have substantial basinwide effects Baseflow loss during in‐stream transport is projected to increase relative to historical conditions